Benefits of Macitentan in Patients with Pulmonary Hypertension: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jinlv Qin; Guizuo Wang; Dong Han (Ubiquity Press, 2023)
Background: This systematic review and meta-analysis aimed to determine the efficacy of macitentan in patients with pulmonary hypertension (PH). Methods: A systematic search was made of PubMed, Embase, Cochrane Library, and clinicaltrials.gov, without language restrictions. Randomized controlled trials (RCTs) on treatment of PH with macitentan, compared with placebo or blank, were reviewed. Studies were pooled to weighted mean differences (WMDs) and risk ratios (RRs), with 95% confidence intervals (CIs). Results: Six RCTs (enrolling 1,003 participants) met the inclusion criteria. Macitentan showed significant effects on 6-min walk distance (6MWD) (WMD 12.06 m, 95% CI 2.12 to 21.99 m), pulmonary vascular resistance (PVR) (WMD -186.51 dyn·s/cm-5, 95% CI -232.72 to -140.29 dyn·s/cm-5), mean pulmonary artery pressure (mPAP) (WMD -3.20 mmHg, 95% CI -5.93 to -0.47 mmHg), N-terminal pro-brain natriuretic peptide (NT-proBNP) (WMD -232.47 ng/L, 95% wCI -318.22 to -146.72 ng/L), and cardiac index (WMD 0.39 L/min/m2, 95% CI 0.20 to 0.58 L/min/m2). Conclusion: Macitentan significantly improved 6MWD, PVR, mPAP, NT-proBNP, and cardiac index in patients with PH. Macitentan should be further validated in patients with PH.